Estimates of stability of desynchronized systems - Stadnik, O. I.; Khusainov, D. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Linear difference systems with lag are considered. The sufficient conditions of stability are established and exponential decay coefficients for solutions are derived. The second Lyapunov method with Razumikhin's condition is used.